2013
DOI: 10.1021/cs400021r
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mechanism of the Cinchoninium Ion Asymmetric Phase-Transfer-Catalyzed Alkylation Reaction

Abstract: The mechanism of the alkylation reaction of the indanone anion through asymmetric phase-transfer catalysis has been unraveled by density functional theory calculations. Our results point out that the present view of the asymmetry induction mechanism determined by hydrogen bond and π–π stacking interactions is not correct. Rather, stabilization of the main reaction pathway takes place through both the hydrogen bond and electrostatic interaction involving the leaving chloride anion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Phase-selective sampling has been achieved by carefully aliquoting a stirred solution and then allowing the immiscible solvents to separate to enable manual sampling from the desired phase. Given that mass transfer between heterogeneous liquids governs the rate of many phase-transfer reactions, arresting agitation may provide a means to “pause” the reaction and allow for sampling. While this approach can facilitate reaction time course analysis, the data acquired may not be reflective of the operational catalytic system under continuous agitation.…”
Section: Introductionmentioning
confidence: 99%
“…Phase-selective sampling has been achieved by carefully aliquoting a stirred solution and then allowing the immiscible solvents to separate to enable manual sampling from the desired phase. Given that mass transfer between heterogeneous liquids governs the rate of many phase-transfer reactions, arresting agitation may provide a means to “pause” the reaction and allow for sampling. While this approach can facilitate reaction time course analysis, the data acquired may not be reflective of the operational catalytic system under continuous agitation.…”
Section: Introductionmentioning
confidence: 99%
“…The quinuclidine moiety is able to activate a nucleophile, and the hydroxyl group can activate an electrophile or assist in the orientation of the substrates via hydrogen bonding. Despite the large number of mechanistic studies by means of nuclear magnetic resonance (NMR), reaction kinetics, and computational techniques, the understanding of the overall mechanisms of Cinchona alkaloid-catalyzed reactions remains limited. ,, In particular, experimental observation of the reaction intermediates is challenging because of the transient and noncovalent nature of the interactions between the catalyst and the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The use of multiple hydrogen bonds to stabilize the anion‐molecule S N 2 transition state (Scheme ) has been envisioned and computationally supported as a promising strategy in supramolecular catalysis . An a posteriori theoretical study of a classical asymmetric phase‐transfer catalyzed process has found this kind of mechanism is operating . In this point, it is important to mention that this kind of activation has not been fully appreciated and its potential use remains poorly explored.…”
Section: Introductionmentioning
confidence: 99%